Optimization of Deep Sedation with Spontaneous Respiration for Therapeutic Endoscopy Combining Propofol and Bispectral Index Monitoring - Kohei Matsumoto; Akihito Nagahara; Kenshi Matsumoto; Yoichi Akazawa; Hiroyuki Komori; Yuta Nakagawa; Tsutomu Takeda; Hiroya Ueyama; Yuji Shimada; Daisuke Asaoka; Mariko Hojo; Sumio Watanabe (Gastroenterology Research and Practice, 2015)
Background/Aims. This study aimed to establish optimal propofol anesthesia for therapeutic endoscopy, which has not been established. Methodology. We retrospectively investigated data on 89 patients who underwent upper-GI endoscopic submucosal dissection or endoscopic mucosal resection under anesthesia with propofol. Examined doses of propofol were changed according to efficacy and/or adverse events and classified into 5 periods. A bispectral index (BIS) monitor was used at Period 5 to decrease the incidence of adverse events caused by oversedation. The initial dose of propofol was administered after bolus injection of pethidine hydrochloride (0.5 mg/kg), and 1.0 mL of propofol was added every minute until the patients fell asleep. Continuous and bolus infusion were performed to maintain sedation. When the patient moved or an adverse event occurred, the maintenance dose examined was increased or decreased by 5 mL/h regardless of body weight. Results. Dose combinations (introduction : maintenance) and patient numbers for each period were as follows: Period 1 (n=27), 0.5 mg/kg : 5 mg/kg/h; Period 2 (n=11), 0.33 mg/kg : 3.3 mg/kg/h; Period 3 (n=7), 0.5 mg/kg : 3.3 mg/kg/h; Period 4 (n=14), 0.5 mg/kg : 2.5 mg/kg/h; Period 5 (n=30), 0.5 mg/kg : 2.5 mg/kg/h, using BIS monitor. During Period 5, an adverse event occurred in 10.0% of patients, which was lower than that for Periods 1–4. Conclusions. Period 5 propofol anesthesia with BIS protocol could be safe and useful for therapeutic endoscopy under deep sedation with spontaneous respiration.